L’art in vivo ou la mythification de la molécule d’ADN - Catherine Voison (Images Re-Vues)
For over a decade some artists are courting science and work in laboratories together with researchers to produce biological entities resulting from the coupling of technology and living mechanisms. Transgenesis and in vivo cellular culture are practices which are used by these who are working in experimentation labs. Those lab-artists make from vegetal, animal and human cells entities which are invisible to the human eye. The material presence of these biological artefacts built beyond the limits of the visible and at the most embryo stage requires certain optical settings which induce a singular encounter with this magical-biological microcosm we are beginning to be familiar with in the artworld. Joe Davis’ infogenes, Eduardo Kac’s petunia and bacterial messages and Marc Quinn’s genomic portrait are such examples which question the visibility of some productions inscribed in the field of biotechnological art.